STRENGTHENING THE ROLE OF RELIGIOUS COURTS IN SHARIA ECONOMIC DISPUTE SETTLEMENT AS A SHARIA ECONOMY DEVELOPMENT EFFORT - Syukri Hidayat (Jurnal Hukum Khaira Ummah, 2022)
The enactment of the Republic of Indonesia Law Number 3 of 2006 concerning the Religious Courts has strengthened the position of the Religious Courts as one of the law enforcement institutions due to the expansion of absolute competence in the settlement of sharia economic disputes. Currently, Islamic economic activities are growing rapidly in Indonesia. This development must be followed by many disputes. The resolution of this dispute is the authority of the Religious Courts, so that the functions of the Religious Courts must be strengthened. The problems discussed in this study include: the extent to which the development of the sharia economy in Indonesia, how to resolve sharia economic disputes in the Religious Courts and how to strengthen the strategy of the function of the Religious Courts. This research is a descriptive normative legal research using a statutory and analytical approach. Based on the results of the study, it can be concluded that the settlement of sharia economic disputes is the absolute authority of the Religious Courts. The settlement process underwent a simple, fast and light update, so a strategy was needed to improve the quality of the Religious Courts. The author suggests that it is necessary to socialize the function and change the stigma about the Religious Courts.Keywords: Sharia Economics, Disputes, Religious Courts.